Electron attachment to DNA and RNA nucleobases: an EOMCC investigation - Dutta, Achintya Kumar; Sengupta, Turbasu; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2015)
We report a benchmark theoretical investigation of both vertical and adiabatic electron affinities of DNA and RNA nucleobases: adenine, guanine, cytosine, thymine, and uracil using equation of motion coupled cluster method. The vertical electron affinity (VEA) values of the first five states of the DNA and RNA nucleobases are computed. It is observed that the first electron attached state is energetically accessible in gas phase. Furthermore, an analysis of the natural orbitals exhibits that the first electron attached states of uracil and thymine are valence-bound in nature and undergo significant structural changes on attachment of an extra electron, which reflects in the deviation of the adiabatic electron affinity (AEA) than that of the vertical ones. Conversely, the first electron attached states of cytosine, adenine, and guanine are in the category of dipole-bound anions. Their structure, by and large, remain unaffected on attachment of an extra electron, which is evident from the observed small difference between the AEA and VEA values. VEA and AEA values of all the DNA and RNA nucleobases are found to be negative, which implies that the first electron attached states are not stable rather quasi bound. The results of all previous theoretical calculations are out of track and shows large deviation with respect to the experimentally measured values, whereas, our results are found to be in good agreement. Therefore, our computed values can be used as a reliable standard to calibrate new theoretical methods. (c) 2015 Wiley Periodicals, Inc.
Keywords: DNA-RNA bases; electron affinity; EOMCC

Electron detachment and subsequent structural changes of water clusters - Das, Susanta; Sengupta, Turbasu; Dutta, Achintya Kumar; Pal, Sourav (Journal of Physical Chemistry A, 2016)
A cost-effective equation of motion coupled cluster method, EOMIP-CCSD(2), is used to investigate vertical and adiabatic ionization potential as well as ionization-induced structural changes of water clusters and compared with CCSD(T), CASPT2, and MP2 methods. The moderate N-5 scaling and low storage requirement yields EOMIP-CCSD (2) calculation feasible even for reasonably large molecules and clusters with accuracy comparable to CCSD(T) method at much cheaper computational cost. Our calculations shed light on the authenticity of EOMIP-CCSD(2) results and establish a reliable method to study of ionization energy of molecular clusters. We have further investigated the performance of several classes of DFT functionals for ionization energies of water clusters to benchmark the results and to get a reliable functionals for the same.

Effect of ligand attachment on the C-I bond dissociation process on aluminum nanoclusters: a DFT investigation - Sengupta, Turbasu; Samanta, Bipasa; Pal, Sourav (Journal of Physical Chemistry C, 2017)
The influence of the ligand attachment on the activation process of carbon halogen bond on small sized aluminum nanoclusters are investigated using density functional theory. Attaching suitable ligand to metal clusters is among the widely popular techniques often used by experimentalists in order to stabilize metastable clusters. In depth theoretical investigations have shown that based on the jellium configuration of the cluster, attaching an electron withdrawing ligand can either make a cluster more reactive toward the C-I dissociation or may convert the cluster relatively inert. The alteration of the activation barriers and other associated parameters due to ligand attachment are included in this paper along with additional calculations and explanations. The study also shows that even the reaction parameters of specific magic clusters can be significantly altered via ligand attachment. The activation process of small molecules on metal clusters are of crucial importance for the development of material science and cluster chemistry. The present investigation will therefore be useful for better understanding of the properties of the ligated clusters as well as may also aid the experimentalists toward controlling the reactivity of a specific cluster as required.